Arquitectura y morfometria de dos especies arboreas en una selva baja caducifolia del sur de Yucatan, Mexico - Interian-Ku, V.M.=700 1 Valdez-Hernandez, J.I.; Garcia-Moya, E.; Romero-Manzanares, A.; Borja-De-La-Rocha, M.A.; Vaquera-Huerta, H.
(Es, En)
Ilus., 43 ref.
Keywords: CAESALPINIA; TAMAÑO; MEDICION; TIPOS DE SUELOS; METODOS ESTADISTICOS; MEXICO; CAESALPINIA GAUMERI; GYMNOPODIUM FLORIBUNDUM; MEDICIONES DASOMETRICAS; SOCIEDAD BOTANICA DE MEXICO